HUBUNGAN SELF-REGULATED LEARNING DAN BERFIKIR KRITIS DENGAN KEMAMPUAN LITERASI DIGITAL DAN LITERASI NUMERASI SEKOLAH DASAR TAHUN PELAJARAN 2024-2025 - Herawati; Cahyani, Isah; Syafruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine the relationship between self-regulated learning and critical thinking with digital literacy and numeracy literacy skills of elementary school students. The subjects of this study were 6th grade students from 5 elementary schools in Bandung Kulon District, with a sample size of 100 students. The research method used was canonical correlation, with data collection procedures including questionnaires to measure self- regulated learning and digital literacy, as well as tests to measure critical thinking and numeracy literacy skills. Canonical assumption tests include normality tests, linearity tests, non-multicollinearity tests, and homogeneity of covariance variance tests. Canonical correlation analysis was carried out through several stages: significanceWilks' Lambda, formation of canonical functions, canonical weight tests (within tests), and canonical loading tests. The results showed that by using the four methods, the significance value was 0.000 (<0.05), which indicated a very statistically significant difference between the groups being compared. The first canonical function has a significance value of 0.000 (<0.05) and the second canonical function has a value of 0.02 (<0.05), both of which are significant. The canonical weight test shows that variables Y1 and Y2 have canonical coefficients exceeding 0.5, with Y1 having a coefficient value of 0.93560 and Y2 of 0.89671. This indicates that Y1 and Y2 have a strong influence in distinguishing groups in this analysis. The canonical loading test shows that the first canonical function has a loading value exceeding 0.5 on variable Y2 (numeracy literacy ability) of 0.93138, and on variable X2 (critical thinking) of 0.95287. The results of this study conclude that there is a significant relationship between self-regulated learning, critical thinking skills, digital literacy, and numeracy literacy. Self- regulated learning and critical thinking skills have been shown to play an important role in improving students' digital literacy and numeracy literacy. ritical thinking plays a major role in mediating this relationship, with a very high canonical loading value. The results of this study confirm that the higher the level of students' critical thinking skills, the greater the influence on improving their numeracy literacy skills. In addition, digital and numeracy literacy are also closely related to self- regulated learning, indicating that good self- regulation skills can strengthen literacy in both aspects. However, this study also reveals that there are still gaps in the literature that need to be explored further, especially in integrating self-regulated learning, critical thinking skills, digital literacy, and numeracy literacy comprehensively. This study makes an important contribution to understanding the dynamics of the relationship between the four aspects and opens up opportunities for further research that can fill the existing gaps, as well as provide deeper insights into the factors that influence students' literacy success in this digital era.